TRANSFORMATION OF INTERNATIONAL ASSISTANCE TO UKRAINE INTO A SECURITY PARTNERSHIP IN NORDIC DEFENCE FORMATS IN 2026–2030 - Myronov, Illia (Public Management and Policy, 2026)
The article examines the tendency of international assistance to Ukraine in Nordic formats to evolve into a more complex model of security partnership in the 2026–2030 perspective. It is shown that the shift from predominantly asymmetric support to more sustainable forms of interaction is driven not only by the quantitative expansion of assistance, but also by qualitative changes in the institutional and security environment, including Finland’s and Sweden’s accession to NATO, the new NORDEFCO Vision 2030, the launch of the enhanced partnership between Ukraine and the Joint Expeditionary Force, and the conclusion of bilateral security agreements between Ukraine and the Nordic states. Based on institutional, comparative, scenario, and analytical-synthetic approaches, and drawing on bilateral security cooperation agreements, NORDEFCO, JEF and NATO documents, governmental decisions on long-term support for Ukraine, and academic studies on regional security, the article substantiates the author’s model of security partnership as a multi-level system with five interrelated contours: military-operational, institutional-coordination, defence-industrial and technological, infrastructure-reconstruction, and political-strategic. It is established that security partnership performs three interrelated functions: strengthening Ukraine’s resilience, enhancing the security of the Nordic and Nordic-Baltic region, and forming common contours of defence cooperation. The scientific contribution of the article lies in conceptualising the transition from the model of assistance to the model of security partnership, structuring its main components, and developing three scenarios for 2026–2030: inertial, functional institutionalisation, and deepened security partnership. The practical significance of the study for Ukraine lies in substantiating the need for consistent implementation of bilateral security agreements, the development of joint defence-industrial projects, the expansion of practical interaction within existing formats, and the combination of security and infrastructure cooperation mechanisms. For the Nordic states, the findings indicate the growing role of the Ukrainian dimension in the ongoing adjustment of the regional security environment and the broader Euro-Atlantic architecture.